Guarantees in Auctions: The Auction House as Negotiator and Managerial Decision Maker - Greenleaf, Eric A.; Rao, Ambar G.; Sinha, Atanu R. (Management Science, 1993)
The multimillion dollar price guarantees that an auction house can offer for paintings have already had a large impact on auction house profits, and place new demands on the auctioneer's decision making and negotiating skills. Yet auctioneers have not been studied as independent entities and decision makers. To create a price guarantee, the auction house and the seller must negotiate both the guarantee amount and the extra commission the seller pays if the auction price exceeds the guarantee. We present a normative model of negotiations and find the frontier of guarantee and commission that is the Nash bargaining solution. We also determine the optimal reserve that the auctioneer should place on guaranteed property. We find that guarantees decrease the auction house's expected revenue compared to a conventional auction, but do allow it to attract business which might otherwise be lost. Guarantees benefit sellers, increasing the expected value and lowering the variance of their auction revenue. The auctioneer's optimal strategy depends not only on the distribution of the artwork's auction price, but also the price it will bring if it fails to sell at auction. In the latter case the auction house must pay the seller the guarantee and then sell the artwork, which it now owns, in a private secondary market where buyers regard the property as “damaged goods” and lower their offers. Although all points on the frontier produce equal expected revenue, several frequently used decision making rules suggest that both parties may prefer a guarantee arrangement where the seller pays no additional commission and the guarantee has the lowest value on the frontier.